2005
DOI: 10.1159/000087214
|View full text |Cite
|
Sign up to set email alerts
|

<i>CYP4V2</i> Mutations in Two Japanese Patients with Bietti’s Crystalline Dystrophy

Abstract: Bietti’s crystalline dystrophy (BCD) is an autosomal-recessive retinal dystrophy characterized by numerous glistening intraretinal dots scattered over the fundus, particularly in the posterior pole. The purpose of this study was to report mutations in the CYP4V2 gene (encoding a ubiquitously-expressed 525-amino acid sequence belonging to the CYP450 family) and to investigate the impact of the mutation on pre-mRNA splicing. DNA and RNA analyses were conducted using blood samples from two unrelated Japanese pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…After the genetic defect was initially linked to chromosome 4q35 (Jiao et al, 2000), Li et al (2004) identified biallelic mutations in the "orphan" P450 enzyme CYP4V2 in 23 of 25 index patients from families with BCD. Numerous research groups (Gekka et al, 2005;Lin et al, 2005;Shan et al, 2005;Wada et al, 2005;Yokoi et al, 2010) confirmed the original genetic findings (Kelly et al, 2011). A recent study demonstrated that more than 95% of all patients with BCD for whom analyses were performed had germline mutations in the CYP4V2 gene (Xiao et al, 2011).…”
Section: Introductionmentioning
confidence: 86%
“…After the genetic defect was initially linked to chromosome 4q35 (Jiao et al, 2000), Li et al (2004) identified biallelic mutations in the "orphan" P450 enzyme CYP4V2 in 23 of 25 index patients from families with BCD. Numerous research groups (Gekka et al, 2005;Lin et al, 2005;Shan et al, 2005;Wada et al, 2005;Yokoi et al, 2010) confirmed the original genetic findings (Kelly et al, 2011). A recent study demonstrated that more than 95% of all patients with BCD for whom analyses were performed had germline mutations in the CYP4V2 gene (Xiao et al, 2011).…”
Section: Introductionmentioning
confidence: 86%
“…More recently, the area of genetic analysis has borne many exciting discoveries. Li et al [22,23] mapped the BCD gene locus to chromosome 4q35.1, and a variety of mutations involving the CYP4V2 gene has since been identified [4,[24][25][26][27]. The CYP4V2 gene is a novel member of the cytochrome P450 group of genes, and it codes for a 525-amino-acid protein active in fatty acid metabolism.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…4,11 Genetic linkage analysis in several BCD families established 4q35-qter as the chromosomal segment harboring the putative causal gene 12 and mutations in CYP4V2 (for cytochrome P450, family 4, subfamily V, polypeptide 2), a gene located within this region, were subsequently identified in a number of patients with the disease. 7,8,13,14 CYP4V2 is composed of 11 exons that encode a widely expressed 525 amino acid CYP450 family member, which is presumably involved in fatty acid metabolism. 7 Approximately 23 different CYP4V2 mutations have been described to date, predominantly in patients from Asia.…”
Section: Introductionmentioning
confidence: 99%